Development of a smart gateway for a label loom machine using industrial IoT technologies - Dionísio, Rogério (2020)
Submitted by Lurdes Grilo (lurdesgrilo@ipcb.pt) on 2020-04-09T11:55:49Z No. of bitstreams: 1 iJOE_vol16_no04_2020_Final.pdf: 1013293 bytes, checksum: 69d550289215595034411c5924fbd17b (MD5)